ANALISIS PENERIMAAN PAJAK PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK WAJIB PAJAK BESAR SETELAH PEMBERLAKUAN KENAIKAN PENGHASILAN TIDAK KENA PAJAK - ERAWATI F, NOVITA Erawati (Jurnal Akuntansi AKUNESA, 2013)
The main of state income from non-oil sector is tax revenues. To increase tax revenues,the government made changes to the non-taxable income. Purpose of this study was todetermine the increase or decrease in tax revenue at Kanwil DJP Wajib Pajak Besarafter the enactment of non-taxable income increases. This study used a qualitativeapproach with a descriptive analysis. Any tax revenues will be processed the datamathematically, and compared from year to year. The results of this study is the taxrevenue, especially income tax Kanwil DJP Wajib Pajak Besar have increasedsignificantly since 2006 until 2009.Keywords: tax revenues, non-taxable income, income tax